I feel wealthy: a major determinant of Portuguese households’ indebtedness? - Camões, F.; Vale, S. (Empirical Economics, 2020)
This paper examines the response of household debt to households’ perception of house prices using data from the first wave of the Household Finance and Consumption Survey. Whereas the literature has hitherto emphasized the effects of housing wealth on consumption, this study concentrates on the effects on debt accumulation—distinguishing mortgage debt from non-mortgage debt and inspecting over-indebtedness. Different measures of housing wealth are considered, controlling for tenure years. The findings reveal that the effects of housing wealth differ by type of loans and with the measure of housing wealth. Over-indebtedness is driven by the same factors that determine mortgage debt, suggesting a strong association between having outstanding liabilities from the primary residence and the risk of entering into default. Further estimations by different income and wealth classes revealed dissimilar housing wealth effects, with non-mortgage debt tending to rise among lower-income households and over-indebtedness tending to be larger among the wealthier.